Chemical composition of leaf cutin in six Quercus suber provenances. (January 2021) - Simões, Rita; Miranda, Isabel; Pereira, Helena
Abstract: The cutin content and composition of cork oak ( Quercus suber ) leaves was determined in six provenances with different seed geographical origin spreading across the species natural distribution. The cutin layer on the leaf surface was on average 518 μg/cm 2 of leaf area and represented 6.7% of the leaf dry weight, with no signiﬁcant diﬀerences among provenances. Cutin depolymerisation was carried out by transesterification on whole leaves. The cutin composition of cork oak leaves is presented here for the first time. It is essentially composed of long-chain aliphatic ω-hydroxy fatty acids (44.4% of the total monomers), mostly with mid-chain hydroxyl and epoxy groups, fatty acids (20.7%), and a smaller proportion of α, ω-dicarboxylic acids (6.5%). The predominant compounds are 10, 16-dihydroxy hexadecanoic acid (17.7–25.2%) and 9, 10, 18-trihydroxyoctadecanoic acid (15.6–18.0%). Alkanols represent 2.8% and aromatic compounds 12.8%, mainly coumarates. Isolation of cuticles from Q. suber leaves was performed using an enzymatic separation procedure and the fragments were analysed. Cuticle isolation is difficult and direct depolymerisation applied to whole leaves proved a suitable method to study cutin monomeric composition, which did not differ substantially to that of the isolated cuticles. No differences between provenances were found regarding cutin content and composition, thereby ruling out a significant genetic determination of these traits, but rather a highly adaptive phenotypic plasticity of cork oak. Although overall similar in their chemical nature, cutin and suberin in cork oak differ in the proportion of the major chemical families, i.e. ω-hydroxy acids, α, ω-diacids, and fatty acids. Graphical abstract: Image 1 Highlights: Cork oak leaf cutin chemical composition reported for the first time. Cutin represents 6.7% of leaf dry mass. Cutin is essentially composed of long-chain aliphatic ω-hydroxy fatty acids. Cutin and suberin differ in the proportion of- ω-hydroxy acids, α, ω-diacids, fatty acids. No between provenances differences were found in cutin content and composition.